Faktor Faktor Kejadian Musculoskeletal Disorders (MDS) Pada Tenaga Kerja Informal (Kuli Panggul) Di Pasar Giwangan Yogyakarta - Lilik Hendrarini; Agus Suwarni (POLTEKKES KEMENKES YOGYAKARTA, 2016)
Giwangan Market in Yogyakarta is a main market for fruits and vegetables which supplies people's daily needs. In addition to sell-and-buy transaction as is in other markets, it is common to find porters carrying fruit and vegetables on their shoulders or on their backs. One of the risks faced by the porters related with those carrying activities is health impact, in the form of musculoskeletal disorders (MDs). To understand whether their working styles are ergonomic or not, analysis on factors of those informal workers are: age, gender, working life, average of the weight which is carried, and frequency of the carrying activities in one time unit, and working posture. The study method used was a cross-sectional designed survey, where those factors or characteristics of the porters were the independent variables and the incidence of MDs was the observed dependent variable. The data of independent variables were collected by using questionnaire, except for working posture, OWAS method was used, and the measurement of MDs employed NBM questionnaire. The data were analyzed with chi-square test at 95 % level of confidence to reveal the significance of relationships among variables under study. The results showed that for working posture, from 102 respondents, 82 porters (80,39 %) were categorized in level 4, i.e. correction for burden carrying technique is urgent to be implemented by now; 13 porters (12,75 %) were categorized in level 3, i.e. that correction is needed as soon as possible. The number of respondents who suffered from severe MDs were 39 persons(38,24 %), moderate MDs were 52 persons (50,98 %) and the rest 11 porters (10,78 %) were of mild MDs. There are significant relationships between age, gender, average of burden weight, and working posture, with the incidence of MDs (p values < 0,05); while frequency of carrying activity and working life, were not found related with the disorders. To implement the correction efforts in carrying style among the porters, the findings of this study furthermore will be informed to the Head of Giwangan Market as well as the related government agencies, in order to prevent the MDs incidence at the very early stage.